PENGARUH SUHU PENGERINGAN DAN UKURAN POTONGAN TERHADAP KARAKTERISTIK TEH KULIT LIDAH BUAYA (Aloe barbadensis Milleer) - Agus Satriadi, I Wayan; Wrasiati, Ni Luh Putu; Lani Triani, I G.Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 2 (2015): Juni, 2015)
This study aimed to (1) determine the effect of drying temperature and size pieces on the characteristics of aloe vera leaves tea, (2) determine the drying tempereture and size pieces of aloe vera leaves te to obtain a good characteristics of tea. The method of this study was a split plot design. Temperature was primary or plot treatment consist of four plot were 60°(±5)C ,70(±5)°C, 80(±5)°C, 90(±5)°Cand size pieces was a split treatment consist of two size ( 100 mm³ and 200 mm³). Observed variables were antioxidant activity, total phenolic, extract content and ash content. Data obtained were analizedby microsoft office exel 2007. The result showed that drying temperature and the size of the chunks effect on antioxidantactivity, total phenolic and extract content but has no effect on ash content. the higher the drying temperature, and the larger the size of the pieces resulting antioxidant activity and total phenolic content decreases but extract content increases. The best treatment is aloe leaf tea with a drying temperature of 60°C and a size of 100 mm³ pieces that have antioxidant activity 17.03% and 26.54 g GAE/100g.
Keywords: 49